Older Patients' Enthusiasm to Use Electronic Mail to Communicate With Their Physicians: Cross-Sectional Survey - Singh, Hardeep; Fox, Sarah A; Petersen, Nancy J; Shethia, Anila; Street, Richard L (JMIR Publications, 2009)
Background Recent evidence indicates increased access to and use of Internet and non-healthcare-related email by older patients. Because email adoption could potentially reduce some of the disparities faced by this age group, there is a need to understand factors determining older patients' enthusiasm to use email to communicate with their physicians. Electronic mail (email) represents a means of communication that, coupled with face-to-face communication, could enhance quality of care for older patients. Objective Test a model to determine factors associated with older patients' enthusiasm to use email to communicate with their physicians. Methods We conducted a secondary data analysis of survey data collected in 2003 for two large, longitudinal, randomized controlled trials. Logistic-regression models were used to model the dichotomous outcome of patient enthusiasm for using email to communicate with their physicians. Explanatory variables included demographic characteristics, health status, use of email with people other than their physician, characteristics of the physician-patient relationship, and physician enthusiasm to use email with patients. Results Participants included a pooled sample of 4059 patients over 65 years of age and their respective physicians (n = 181) from community-based practices in Southern California. Although only 52 (1.3%) patient respondents reported that they communicated with their physician by email, about half (49.3%) expressed enthusiasm about the possibility of using it. Odds of being enthusiastic decreased with increased age (by 0.97 for each year over 66) but were significantly higher in African Americans (OR = 2.1, CI = 1.42 - 3.06), Hispanics (OR = 1.6, CI = 1.26 - 2.14) and men (OR = 1.3, CI = 1.1 - 1.5). Conclusions Despite perceived barriers such as limited access to the Internet, older patients seem to want to use email to communicate with their physicians.